Seriousness at Work and Its Relationship to the Six Big Factors of Personality in Light of the (HEXACO-60) Model Among a Sample of Employees at the Commercial Bank of Syria (Damascus University Journal of educational and Psychologyical sciences, 2026)
The current research aims to identify the level of seriousness at work, and to identify the six most common major factors. and to verify the possibility of predicting seriousness at work through the six big factors of personality, and to identify the relationship between seriousness at work and the six big factors of personality, and to reveal the differences between the average scores of individuals in a sample of employees at the Commercial Bank of Syria on the scales of (seriousness at work, and the six big factors of personality) according to the variables: (gender, number of years of experience). For this purpose, the researcher chose a sample consisting of (150) male and female workers. The seriousness scale was used in the work and the big six personality factors scale (HEXACO-60).The most important results reached by the current research: The level of seriousness at work among the members of the research sample was average with respect to the sub-dimensions and the total score, and the most common of the six big factors of personality among the members of the research sample came in the following order: (agreeableness, conscientiousness, extraversion, openness to experience, honesty-humility, emotionality), and that seriousness at work can be predicted through the six big factors of personality. The results also showed a negative inverse correlation with the factor (emotionality), and a positive correlation with the rest of the factors, and the presence of statistically significant differences on the scale of seriousness at work according to the variables: (gender, number of years of experience). The presence of statistically significant differences on the scale of the six big factors of personality according to the gender variable, and the absence of statistically significant differences according to the number of years of experience variable.
Keywords: Seriousness At Work; Six Big Factors Of Personality; Employees At The Commercial Bank Of Syria